Challenges of Implementation E-Learning Platforms in Iraqi Universities - Nazhat AbdulRazak; Mariam Ali (Engineering and Technology Journal, 2019)
The great development in the field of information and communication technology (ICT) moved the education reality to a new horizon, where the internet touches almost all aspects of digital learning, we are currently experiencing the existence of electronic platforms in  large extent, especially in the field of electronic learning (E-learning), The existence of these platforms stems from the importance of education in general and the importance of transferring the educational process to electronic areas to facilitate learning, in particular, This research aims to target the problems experienced by e-learning in Iraq and offer some recommendations that may contribute to reducing this delay to promote educational reality. An electronic questionnaire was published for students and teaching staff, in which 30 questions was asked. The number of samples participating in the questionnaire was 100 Professors, students, and teachers. Results of the questionnaire showed that they have fully sentient of the essential implementation of electronic learning and its delay reasons.